Spectral light absorption by ambient aerosols influenced by biomass burning in the Amazon Basin. I: Comparison and field calibration of absorption measurement techniques - O. Schmid; O. Schmid; P. Artaxo; W. P. Arnott; D. Chand; L. V. Gatti; G. P. Frank; A. Hoffer; M. Schnaiter; M. O. Andreae (Atmospheric Chemistry and Physics, 2006)
Spectral aerosol light absorption is an important parameter for the assessment of the radiation budget of the atmosphere. Although on-line measurement techniques for aerosol light absorption, such as the Aethalometer and the Particle Soot Absorption Photometer (PSAP), have been available for two decades, they are limited in accuracy and spectral resolution because of the need to deposit the aerosol on a filter substrate before measurement. Recently, a 7-wavelength (λ) Aethalometer became commercially available, which covers the visible (VIS) to near-infrared (NIR) spectral range (λ=450–950 nm), and laboratory calibration studies improved the degree of confidence in these measurement techniques. However, the applicability of the laboratory calibration factors to ambient conditions has not been investigated thoroughly yet. As part of the LBA-SMOCC (Large scale Biosphere atmosphere experiment in Amazonia – SMOke aerosols, Clouds, rainfall and Climate) campaign from September to November 2002 in the Amazon basin we performed an extensive field calibration of a 1-λ PSAP and a 7-λ Aethalometer utilizing a photoacoustic spectrometer (PAS, 532 nm) as reference device. Especially during the dry period of the campaign, the aerosol population was dominated by pyrogenic emissions. The most pronounced artifact of integrating-plate type attenuation techniques (e.g. Aethalometer, PSAP) is due to multiple scattering effects within the filter matrix. For the PSAP, we essentially confirmed the laboratory calibration factor by Bond et al. (1999). On the other hand, for the Aethalometer we found a multiple scattering enhancement of 5.23 (or 4.55, if corrected for aerosol scattering), which is significantly larger than the factors previously reported (~2) for laboratory calibrations. While the exact reason for this discrepancy is unknown, the available data from the present and previous studies suggest aerosol mixing (internal versus external) as a likely cause. For Amazonian aerosol, we found no absorption enhancement due to hygroscopic particle growth in the relative humidity (RH) range between 40% and 80%. However, a substantial bias in PSAP sensitivity that correlated with both RH and temperature (T) was observed for 20%<RH<30% and 24°C<T<26°C, respectively. In addition, both PSAP and Aethalometer demonstrated no sensitivity to gaseous adsorption. Although very similar in measurement principle, the PSAP and Aethalometer require markedly different correction factors, which is probably due to the different filter media used. Although on-site calibration of the PSAP and Aethalometer is advisable for best data quality, we recommend a set of "best practice" correction factors for ambient sampling based on the data from the present and previous studies. For this study, the estimated accuracies of the absorption coefficients determined by the PAS, PSAP and Aethalometer were 10, 15 and 20% (95% confidence level), respectively.